Implementation Of Management Of Facilities And Extracurricular Infrastructure For Student Sports At The Modern Islamic Boarding School Ar-Rahmat Bojonegoro - Nabhan, Aqib Khoiron; Syaefudin, Syaefudin; Choironi, Mohammad Afif; Mohd Yusof, Siti Ilyana Binti (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This research was motivated by the lack of facilities and infrastructure for extracurricular activities at the Ar-Rahmat Bojonegoro Modern Islamic Boarding School. Even though it only has one field, the field is used for various activities. The students are still able to achieve achievements through extracurricular activities, especially in sports. This research aims to investigate the implementation of the management of extracurricular sports facilities and infrastructure as well as supporting and inhibiting factors. The research uses qualitative methods with a descriptive analysis approach. Sampling was carried out using a purposive sampling technique. Data was collected through interviews, observation, and documentation. Data analysis was carried out using the stages of Transcript, Coding, Grouping, Comparing Contrasting, and Interpretation. The validity of the data is strengthened by source triangulation. The research results show that the management of facilities and infrastructure can run smoothly according to the vision and mission of the Ar-Rahmat Bojonegoro Modern Islamic Boarding School. The process involves planning, organizing, implementing, and monitoring. Supporting factors for implementation include quality human resources, internal school cooperation, external assistance, as well as awareness and participation of students and teachers. Inhibiting factors include lack of field space, incidental programs not included in the work program, budget limitations, and decisions that depend on foundation policy. Limited funds are also an obstacle because they only rely on donations from student guardians without government support.